1994
DOI: 10.1213/00000539-199402000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Local Infiltration with Ropivacaine for Postoperative Pain Relief After Cholecystectomy

Abstract: In a randomized, double-blind, placebo-controlled trial, we evaluated the use of preoperative local anesthesia with regard to postoperative pain. Before surgery in 66 patients scheduled for cholecystectomy, the abdominal wall along the proposed line of incision was infiltrated with 70 mL of 0.25% ropivacaine, 70 mL of 0.125% ropivacaine, or 70 mL of saline. Wound pain at rest, wound pain during mobilization, and pressure exerted to reach maximum pain tolerance were assessed after 6, 26, 50, and 74 h and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 6 publications
3
39
0
10
Order By: Relevance
“…Some studies have reported the efficacy of such "preemptive analgesia" in laboratory animals following pre-surgical administration of opioids or of a local anesthetic (5-7). However, a local anesthetic before or soon after the end of surgery did not change the intensity of pain produced by herniorrhaphy (8) or cholecystectomy (9). Also, differences in the post-surgical pain were not detected in patients submitted to caudal or epidural block, or treated with systemic administration of opioids before or after surgery (10).…”
Section: Introductionmentioning
confidence: 87%
“…Some studies have reported the efficacy of such "preemptive analgesia" in laboratory animals following pre-surgical administration of opioids or of a local anesthetic (5-7). However, a local anesthetic before or soon after the end of surgery did not change the intensity of pain produced by herniorrhaphy (8) or cholecystectomy (9). Also, differences in the post-surgical pain were not detected in patients submitted to caudal or epidural block, or treated with systemic administration of opioids before or after surgery (10).…”
Section: Introductionmentioning
confidence: 87%
“…In comparing preemptive and postoperative infiltration, it was observed 72% decrease in morphine consumption (1.5 mg versus 5.5 mg) (p < 0.005). Similarly, in a different study 17 , the amount of requested analgesics in the first 24 hours was significantly lower in patients submitted to inguinal hernia repair with ropivacaine infiltration. Similarly, wound infiltration with ropivacaine in laparoscopic cholecystectomy and hernia repair induces satisfactory postoperative analgesia decreasing the need for opioids 20,21 .…”
Section: Discussionmentioning
confidence: 69%
“…However, although 0.25% and 0.5% concentrations and lower ropivacaine doses have provided effective analgesia after 3 hours, they were less effective in terms of duration, since after 6 hours pain intensity was lower than control only for the 0.5% group. However, 0.125% solution was not more effective than placebo 17,18 . In our study, preemptive and postoperative ropivacaine infiltration has decreased pain intensity, however effectiveness was better with preemptive infiltration.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to this hypothesis, local infiltration and the resulting nerve impulse block prevent nociceptive impulses from reaching the CNS and suppress the sustained state of hyperexcitability responsible for intense postoperative pain [12].…”
Section: Discussionmentioning
confidence: 99%